Histological and immunohistochemical study of hepatitis B virus in human immunodeficiency virus infection. Issue 3 (March 1990) - Goldin, R D; Fish, D E; Hay, A; Waters, J A; McGarvey, M J; Main, J; Thomas, H C
Abstract : Because the risk factors for human immunodeficiency virus (HIV) infection and hepatitis B (HBV) are similar and therefore coinfection is not uncommon, a detailed histological and immunohistochemical study of chronic hepatitis B infection in a group of 20 HIV positive Caucasian males (who did not have AIDS) and 30 HIV negative controls were undertaken. Using both the conventional histological classification and the Knodell histological activity index it was shown that HIV negative patients were more likely to have active disease and also more scarring than HIV positive patients. Hepatitis B surface antigen (HBsAg) expression was not significantly different between the two groups but expression of hepatitis Be antigen (HBeAg) and HBV-DNA polymerase was greater in those who were HIV positive. HIV positive patients are therefore more likely to have immunohistochemical markers of active viral replication, although histologically, liver disease is less severe. These findings have important implications for assessing the biopsy specimens in this group of patients and for treatment strategies aimed at improving their immune function.